Keterlibatan Pelanggan dan Antesedennya pada Transaksi E-Commerce pada Generasi Z - Erlita Ridanasti (Fakultas Ekonomi Universitas Islam 45, 2021)
ABSTRACT The purpose of this study was to determine the effect of Customer Involvement on Customer Participation in e-commerce transactions in Generation Z; to determine the effect of Customer Involvement on Customer Experience in e-commerce transactions in Generation Z; to determine the effect of Customer Participation on Customer Engagement in e-commerce transactions in Generation Z; to determine the effect of Customer Experience on Customer Engagement on e-commerce transactions in generation Z and to determine the effect of Customer Involvement on Customer Engagement on e-commerce transactions in generation Z. This study uses a sample of people who have made purchases at e-commerce in Tokopedia/Shopee with a sampling technique in the form of non-probability sampling and obtained a sample of 213 respondents. While the data analysis technique used SEM AMOS. The results of the analysis and discussion can be concluded that Customer Involvement has a positive effect on Customer Engagement, Customer Involvement has a positive effect on Customer Experience, Customer Participation has no positive effect on Customer Engagement, Customer Experience has a positive effect on Customer Engagement and Customer Involvement has a positive effect on Customer Engagement Keywords: Customer Involvement, Customer Participation, Customer Engagement and Customer Experience